2019
DOI: 10.2134/jeq2019.03.0103
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Overland and Tile Flow to Runoff and Nutrient Losses from Vertisols in Manitoba, Canada

Abstract: This study quantified the contributions of overland and tile flow to total runoff (sum of overland and tile flow) and nutrient losses in a Vertisolic soil in the Red River valley (Manitoba, Canada), a region with a cold climate where tile drainage is rapidly expanding. Most annual runoff occurred as overland flow (72-89%), during spring snowmelt and large spring and summer storms. Tile drains did not flow in early spring due to frozen ground. Although tiles flowed in late spring and summer (33-100% of event fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 43 publications
4
25
1
Order By: Relevance
“…Our results provide insight into how preferential flow contributions are affected by desiccation crack networks that bypass the drainage layer during the growing season. Surface runoff was second greatest in the summer, which agrees well with other recent studies that have shown that high‐intensity rainfall on clay soils can trigger infiltration‐excess surface flow with either simultaneous or zero tile response (e.g., Kokulan, Macrae, Lobb, & Ali, 2019; Macrae et al., 2019). We found that quickflow contributions constituted 80% of tile flow during summer months, suggesting simultaneous connectivity of surface and tile pathways, which occurs in spring and summer in clay soils (Macrae et al., 2019).…”
Section: Discussionsupporting
confidence: 90%
“…Our results provide insight into how preferential flow contributions are affected by desiccation crack networks that bypass the drainage layer during the growing season. Surface runoff was second greatest in the summer, which agrees well with other recent studies that have shown that high‐intensity rainfall on clay soils can trigger infiltration‐excess surface flow with either simultaneous or zero tile response (e.g., Kokulan, Macrae, Lobb, & Ali, 2019; Macrae et al., 2019). We found that quickflow contributions constituted 80% of tile flow during summer months, suggesting simultaneous connectivity of surface and tile pathways, which occurs in spring and summer in clay soils (Macrae et al., 2019).…”
Section: Discussionsupporting
confidence: 90%
“…However, the effect of drainage tiles on water partitioning between surface runoff and subsurface drainage has been found to vary with regions. This is well demonstrated by the contrasting findings of Plach et al (2019) in the Great Lakes region and Kokulan et al (2019) in the northern Great Plains. Although snowmelt dominates annual runoff and nutrient loads in both regions, tile drainage dominates year‐round runoff in the Great Lakes region (Plach et al, 2019), whereas it contributes a very small proportion of year‐round runoff in the Vertisolic clays of the Red River valley where most runoff occurs on frozen soils (Kokulan et al, 2019).…”
Section: Management Options For Agricultural Water Quality In Cold CLmentioning
confidence: 90%
“…Frozen or partially frozen ground impedes infiltration of rainfall or melting snow (Gray et al., 2001), increasing the potential for surface ponding and overland flow. In colder regions found outside of the Great Lakes Region, such as the Northern Great Plains, there is extensive ground frost, and snowmelt runoff primarily flows as overland flow on frozen ground (Dumanski et al., 2015) and tile drains are decoupled from the surface by frost (Kokulan, Macrae, Ali, et al., 2019; Kokulan, Macrae, Lobb, et al., 2019). However, tile drains in the more temperate Lake Erie region do not appear to be decoupled from the surface by frozen ground because they tend to flow throughout the year (Pease et al., 2018; Plach et al., 2019), although infiltration can still be impeded by ground frost.…”
Section: Geographical Factors Influencing Vulnerability To P Loss: Regional Differences In Climate Geomorphology Farming Systems and Artimentioning
confidence: 99%